Modular modeling and its applications in studies of grazing effects - Miao, Zhongqi, author; Boone, Randall, advisor; Conant, Richard, committee member; Ocheltree, Troy, committee member (Colorado State University. Libraries, 2016)
Grazing is an important ecosystem process that can affect the grazing system at different levels. Overall grazing effect can be a combination of various direct and indirect effects. It is difficult to study grazing with all of the effects considered. To have a better knowledge of grazing effects and animal-plant interactions, modeling is one important pathway to achieve this goal. People usually use a diversity of approaches when modeling grazing based on different objectives, which makes model evaluations and comparisons difficult. With modular modeling, where different model components are regarded as separate and standardized modules, this situation can be changed. An example model is developed using a modular approach. It included most of the grazing effects and switches that can turn these effects on and off. This model was designed to be capable for applications with different hypothesis and objectives. It is expected to be clearer for people who are not familiar to models to make comparisons and evaluations of grazing effects. To test the feasibility of the model, a theoretical experiment on compensatory behavior in grassland production and a realistic simulation on plant-animal interactions in Qinghai-Tibetan plateau, China, are conducted. The results of these two applications demonstrate the benefits of using modular modeling in studies of grazing effects.